Analisis Yuridis Perbedaan Kritik Dengan Pencemaran Nama Baik Dalam Kuhp Dan Undang-Undang Nomor 1 Tahun 2024 Tentang Informasi Dan Transaksi Elektronik (ITE) - Pasaribu, Audry Salsabila; Muhamad Radjhu Khan Saputra; Ilham Rahman Prayogo; Taun Taun (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses a legal analysis of the differences between criticism and defamation in Indonesian law, especially in the Criminal Code (KUHP) and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE). The research method used is normative legal with a regulatory and contextual approach. The results of the study show that the Criminal Code and the ITE Law both provide protection for individual honor, but differ in the scope of application. The Criminal Code focuses more on conventional interactions, while the ITE Law regulates the electronic realm. Although it aims to protect the name well, the provisions in the ITE Law are considered to have weaknesses due to the potential for multiple interpretations that can threaten freedom of expression. Therefore, a proportional legal interpretation is needed to maintain a balance between protection of personal honor and respect for freedom.